2008
DOI: 10.1097/01.aoa.0000308292.53166.94
|View full text |Cite
|
Sign up to set email alerts
|

Disruptive Behavior in Obstetrics: A Hidden Threat to Patient Safety

Abstract: A serious threat to patient safety-which is based on effective communications and interdisciplinary teamwork-is disruptive or intimidating behavior on the part of healthcare professionals. Prior to this study, there were no reports on such behavior in labor and delivery units. Thus, the author investigated disruptive and intimidating behavior in the obstetric setting in the states of Oregon, Washington, and California and the effects of such behavior on patient safety.In October 2005, questionnaires were sent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 0 publications
0
11
0
2
Order By: Relevance
“…Health‐care workers have associated incidences of inappropriate behaviours, such as bullying, with potential or actual errors, specific adverse outcomes and patient mortality (Rosenstein & O'Daniel , , Farrell et al . , Veltman ). When work relationships are not examined properly, they may lead to medical errors, hospital‐acquired infections, patient readmissions and nurse turnover (American Association of Critical‐Care Nurses ).…”
Section: Bullying In the Work Environmentmentioning
confidence: 99%
“…Health‐care workers have associated incidences of inappropriate behaviours, such as bullying, with potential or actual errors, specific adverse outcomes and patient mortality (Rosenstein & O'Daniel , , Farrell et al . , Veltman ). When work relationships are not examined properly, they may lead to medical errors, hospital‐acquired infections, patient readmissions and nurse turnover (American Association of Critical‐Care Nurses ).…”
Section: Bullying In the Work Environmentmentioning
confidence: 99%
“…In a recent study, intimidating behavior demonstrated by professionals in labor and delivery units included angry outbursts; rudeness; verbal attacks; physical threats or aggressive physical contact; violation of policies; sexual harassment; idiosyncratic, inconsistent, or passive aggressive orders; derogatory comments about the organization; and disruption of smooth function of the health care team (Veltman, 2007). Although physicians displayed the largest incidence of disruptive behavior (in 69.1% of cases) nurses’ behavior was disruptive in the remaining 30.9%.…”
Section: Prevalence and Effects Of Disruptive Behaviors In The Workplacementioning
confidence: 99%
“…Conversations in Obstetrics, and TeamSTEPPS have been widely promoted as a means of effectively conveying information among members of the patient care team . Despite literature that establishes a connection between diminished safety associated with incivility, intimidation, and disruptive behavior, these behaviors still exist on perinatal units . Strong emphasis on establishing “psychological safety” as a cultural imperative on every perinatal unit is a key to allowing dialogue regarding patient care to occur seamlessly:
Team climate must be “characterized by interpersonal trust and mutual respect in which people are comfortable in being themselves.
…”
Section: Alertmentioning
confidence: 99%